2019
DOI: 10.1186/s12984-019-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

Adapting myoelectric control in real-time using a virtual environment

Abstract: BackgroundPattern recognition technology allows for more intuitive control of myoelectric prostheses. However, the need to collect electromyographic data to initially train the pattern recognition system, and to re-train it during prosthesis use, adds complexity that can make using such a system difficult. Although experienced clinicians may be able to guide users to ensure successful data collection methods, they may not always be available when a user needs to (re)train their device.MethodsHere we present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…The 400g load, representing a lightweight prosthesis, was attached throughout training. This is an adaptation of a method suggested in previous studies [22], [23], [25], [27].…”
Section: B Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…The 400g load, representing a lightweight prosthesis, was attached throughout training. This is an adaptation of a method suggested in previous studies [22], [23], [25], [27].…”
Section: B Experimental Protocolmentioning
confidence: 99%
“…2) Real-Time Testing Protocol: In each session, subjects completed a set of 3D VR TAC tests that were based on previous work [23]. Each test comprised one trial for each movement class (except 'no movement') in each limb position.…”
Section: B Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Batzianoulis et al (2018) verified that dynamic training data collected during the reach-to-grasp phase of the prehension improved myocontrol stability during an online pick-and-place task. Similarly, Yang et al (2017a) and Woodward and Hargrove (2019) acquired training sEMG data while moving the arm and tested the resulting myocontrol models by engaging the participants in online tests derived from, respectively, the target achievement control and the box-and-blocks tests. Both studies confirmed that the performance of myocontrol in online settings improves when the training data is acquired while changing the arm configuration rather than keeping the arm steady in one position.…”
Section: Introductionmentioning
confidence: 99%